Review of Long-Term Performance of Timber-Concrete Composite Beams - Peiyang Liu; Hao Du; Zheng Chen; Xiamin Hu (BioResources)
Timber-concrete composite (TCC) beams are formed by integrating timber beams and concrete slabs into a cohesive structural unit using shear connectors. This integration capitalizes on the tensile strength of timber and the compressive strength of concrete, resulting in excellent load-bearing capacity, bending stiffness, vibration comfort, sound insulation, and fire resistance. The long-term behavior of TCC beams must be emphasized, considering the significant time-dependent behaviors of timber, concrete, and the connection system. This work analyzed the long-term mechanical behavior of TCC beams and systematically reviewed the current research on the long-term performance. The primary focus was on the experimental studies of the shear performance of the shear connectors and the mechanical performance of TCC beams under long-term loads. Furthermore, theoretical methods and numerical simulation analyses for evaluating the long-term performance of TCC beams were analyzed. Strengths and weaknesses of existing theoretical methods are identified, and further research and development in the calculation method of TCC beams under long-term loads is proposed.